Progress in search for high‐redshift galaxies magnified by gravitational lensing. Issue 4 (2nd May 2013) - Zheng, W.; Bradley, L.; Zitrin, A.; Moustakas, J.; Postman, M.; Ford, H.; Shu, X.; Coe, D.; Moustakas, L.A.; Koekemoer, A.; Milino, A.; Jouvel, S.; et al.
Abstract Our searches in the CLASH data have found many high‐redshift galaxy candidates. One object at z = 6.2 in MACS J0329‐02 is quadruply lensed. Another object in MACS J1149+22 is at redshift z = 9.6 and AB = 25.7, the first candidate at z > 9 that is bright enough for spectroscopic observations. The discovery of more than 80 galaxy candidates at z > 7 demonstrates the unique potential of galaxy cluster fields for finding highly magnified, intrinsically faint galaxies at the highest redshifts. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)